Clinical insights into duodenal-type follicular lymphoma: case series study - A Reum Choe; Ye Ji Jun; Min-Sun Cho; Chung Hyun Tae; Sung-Ae Jung; Ki-Nam Shim (Clinical Endoscopy)
In Asia, widespread early detection through endoscopic screening has resulted in higher diagnosis rates of asymptomatic duodenal-type follicular lymphoma (DFL). However, no standardized guidelines exist for diagnosing and managing DFL, and ongoing debates persist regarding the optimal treatment strategies. This retrospective observational study was conducted between February 2018 and July 2024. Endoscopic examination revealed small whitish nodular lesions in the second portion of the duodenum. Seven patients (58.0%) underwent involved-site radiation therapy. Two patients (17.0%) with stage IV disease underwent chemotherapy with rituximab combined with cyclophosphamide, doxorubicin, vincristine, and prednisolone. Another two (17.0%) received chemotherapy with rituximab combined with cyclophosphamide, vincristine, and prednisone. One patient (8.0%) was treated with rituximab monotherapy. During a median follow-up of 30.2 months, no cases of disease progression were observed. Although radiation and chemotherapy are effective treatments, the slow progression of the disease may make a watch-and-wait strategy appropriate.